G20 Summit Coverage on Television Media: Quantitative Framing Analysis on Three National Television News Programs (article has been withdrawn by author) - Irwanti, Marlinda; Morissan, Morissan (Pancasila International Journal of Applied Social Science, 2024)
Article has been withdrawn by author